2019
DOI: 10.3389/fchem.2019.00021
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Growth of Black Phosphorus in Sn-I Assisted Reactions

Abstract: Black phosphorus, an emerging layered material, exhibits promising applications in diverse fields, ranging from electronics to optics. However, controlled synthesis of black phosphorus, particularly its few-layered counterparts, is still challenging, which should be due to the unclear growth mechanism of black phosphorus. Here, taking the most commonly used Sn-I assisted synthesis of black phosphorus as an example, we propose a growth mechanism of black phosphorus crystals by monitoring the reactions and analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 30 publications
2
51
0
2
Order By: Relevance
“…Subsequently, the morphology and crystalline structure of the bulk BP was further characterized using a transmission electron microscope (TEM) image. As shown in Figure 1c,d, a ribbon-like structure was clearly observed with a clear lattice spacing of 0.218 nm, corresponding to the (002) planes of BP crystals, which is good in relation to previously reported values of BP single crystals [21][22][23]. To further confirm the characteristics of the BP crystals, selected area electron diffraction (SAED) was conducted ( Figure 1e, upper right inset of Figure 1d), which demonstrated the excellent crystallization of the corresponding materials.…”
Section: Synthesis Of High-quality Bp Single Crystalssupporting
confidence: 89%
See 2 more Smart Citations
“…Subsequently, the morphology and crystalline structure of the bulk BP was further characterized using a transmission electron microscope (TEM) image. As shown in Figure 1c,d, a ribbon-like structure was clearly observed with a clear lattice spacing of 0.218 nm, corresponding to the (002) planes of BP crystals, which is good in relation to previously reported values of BP single crystals [21][22][23]. To further confirm the characteristics of the BP crystals, selected area electron diffraction (SAED) was conducted ( Figure 1e, upper right inset of Figure 1d), which demonstrated the excellent crystallization of the corresponding materials.…”
Section: Synthesis Of High-quality Bp Single Crystalssupporting
confidence: 89%
“…Therefore, it can be concluded that BP single crystals were successfully fabricated using this mineralization route, endowing the possibility of precise analysis and application without purification in the future. Nanomaterials 2020, 10 3 of 9 spacing of 0.218 nm, corresponding to the (002) planes of BP crystals, which is good in relation to previously reported values of BP single crystals [21][22][23]. To further confirm the characteristics of the BP crystals, selected area electron diffraction (SAED) was conducted ( Figure 1e, upper right inset of Figure 1d), which demonstrated the excellent crystallization of the corresponding materials.…”
Section: Synthesis Of High-quality Bp Single Crystalssupporting
confidence: 83%
See 1 more Smart Citation
“…During the reaction, the Sn 24 P 22− x I 8 compound, exhibiting a clathrate structure with sufficient P vacancies, not only allows the reaction of P 4 with the host structure, but also permits excess P atoms to diffuse out from the host structure to form BP. Our recent exploration also demonstrated that Sn 24 P 19.3 I 8 was a common intermediate in all the Sn–I mineralized systems, and the black phosphorus crystals were proposed to be formed with the assistance of SnI 2 , following a polymerization‐like process …”
Section: Cvt Based Synthesis Of Black Phosphorusmentioning
confidence: 86%
“…The complexity of mechanical exfoliation would be a considerable barrier towards the practical application of such a kind of device, as the large-scale growth technology of BP is not available yet. 31 Moreover, atmospheric stability issue of the devices is not clearly addressed in previous reports. Considering that BP is very unstable in air, 10,32,33 the atmospheric stability of the device must be taken into account for relevant exploration.…”
Section: Introductionmentioning
confidence: 96%